2011
DOI: 10.1002/jor.21466
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of serum proteomes of degenerative scoliosis

Abstract: Degenerative scoliosis (DS) is an important degenerative lumbar disease causing spinal dysfunction and affecting the quality of life of the elderly, and is associated not only with severe back or leg pain but also with complicated surgical outcomes. The pathogenesis of DS is still unknown. Therefore, it is very important to ascertain the etiology of degenerative scoliosis and establish related molecular markers predicting and controlling the scoliosis. For the first time, we used two-dimensional fluorescence D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Proteins that are involved in pain are important to investigate due to the fact that they can act as signal substances, activate the formation of algesics and control nociceptive processes. The number of studies investigating the human proteome in body fluids and tissues in human chronic pain conditions are limited e.g., [17][22], [35][37]. There are also a few examples of proteomic studies in acute pain e.g., acute coronary syndrome [38], after eccentric exercises [39] and experimental cutaneous injury [40].…”
Section: Discussionmentioning
confidence: 99%
“…Proteins that are involved in pain are important to investigate due to the fact that they can act as signal substances, activate the formation of algesics and control nociceptive processes. The number of studies investigating the human proteome in body fluids and tissues in human chronic pain conditions are limited e.g., [17][22], [35][37]. There are also a few examples of proteomic studies in acute pain e.g., acute coronary syndrome [38], after eccentric exercises [39] and experimental cutaneous injury [40].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the rapid increase of prevalence of ADS, more and more attention have been paid to this disease, including the researches of etiology, 4 , 5 patients’ demographics, 6 clinical and radiological evaluation, 7 conservation treatment and surgery. 8 10 Only a few studies 3 , 6 , 11 have been performed to make a description of some patients’ demographics and radiographic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic analyses of the sera of patients with DS have identified 11 proteins that are differentially expressed in such patients, 2 of which were secondarily confirmed with Western blot analyses, CLU (also known as apolipoprotein J, testosterone-repressed prostate message-2, SP 40-40, complement lysis inhibitor, gp80, glycoprotein III, and sulfate glycoprotein-2) and Ficolin-3 (also named Hakata antigen, thermolabile β-2 macroglycoprotein, thermolabile substance, and H-ficolin) (83). Both of these proteins have been suggested to have roles in autoimmunity, although they both likely have multiple roles in the human body and their association is non-specific.…”
Section: Degenerative Lumbar Scoliosismentioning
confidence: 79%
“…It is thought that distinct genetic characteristics define these seemingly similar, but quite clinically different syndromes. Our systematic review identified six works in the literature (Table 2) (52, 8387) that identified genetic contributions for DS. The quality of the data is relatively limited (Level III studies) but provides some insight into potential genetic mechanisms for disease pathogenesis that could potentially be used in future studies.…”
Section: Degenerative Lumbar Scoliosismentioning
confidence: 99%